1998
DOI: 10.1200/jco.1998.16.8.2625
|View full text |Cite|
|
Sign up to set email alerts
|

Mortality from myocardial infarction after adjuvant radiotherapy for breast cancer in the surveillance, epidemiology, and end-results cancer registries.

Abstract: Adjuvant RT for left-sided breast cancer diagnosed in women younger than 60 years of age is associated with a higher risk for fatal MI 10 to 15 years later compared with adjuvant RT for right-sided cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
124
2
10

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(142 citation statements)
references
References 30 publications
6
124
2
10
Order By: Relevance
“…The chronic toxicity of heart disease mortality from thoracic radiation has been studied in patients with lymphoma and breast cancer. [26][27][28] Of particular relevance to our results is a report by Giordano et al 29 suggesting that patients with breast cancer who were treated with older technology (1973)(1974)(1975)(1976)(1977)(1978)(1979) experienced an increase in radiotherapy-associated heart disease mortality compared with patients who were treated in more recent years. This finding did not begin to emerge until 10 years of follow-up had been established.…”
Section: Discussionmentioning
confidence: 49%
“…The chronic toxicity of heart disease mortality from thoracic radiation has been studied in patients with lymphoma and breast cancer. [26][27][28] Of particular relevance to our results is a report by Giordano et al 29 suggesting that patients with breast cancer who were treated with older technology (1973)(1974)(1975)(1976)(1977)(1978)(1979) experienced an increase in radiotherapy-associated heart disease mortality compared with patients who were treated in more recent years. This finding did not begin to emerge until 10 years of follow-up had been established.…”
Section: Discussionmentioning
confidence: 49%
“…However, by their very nature, surrogate measurements for these risk factors are not as good as actual measurements and some residual confounding is likely. Nevertheless, in a recent review on circulatory disease and radiation effects (16), in those studies that had additional information on some of these risk factors (9,(34)(35)(36), ERR/Sv estimates were virtually unchanged when additional adjustment for these factors was made.…”
Section: Discussionmentioning
confidence: 99%
“…There is documented evidence of a dose-related excess risk of circulatory disease in Japanese atomic bomb survivors (4)(5)(6)(7). At higher, yet still moderate dose rates, studies of patients treated by radiotherapy of the left breast also demonstrate clear evidence of subsequent cardiovascular disease mortality risk several years postirradiation (8)(9)(10)(11)(12). Circulatory disease is not the only non-cancer disease that may be a late effect of radiation exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Rutqvist and Johansson (1990) reported that radiation therapy for left-sided breast cancer given in 1970 -1980 resulted in a statistically significant higher mortality due to MI. Paszat et al (1998) reported an association of radiation therapy with fatal MI in women with left-sided cancer diagnosed from 1973 -1992, particularly among women under age 60 years. Yet two studies of women treated in the 1980s reported no association of radiation therapy with MI morbidity or mortality (Hojris et al, 1999;Vallis et al, 2002).…”
Section: Discussionmentioning
confidence: 99%